The effect of duodenogastric reflux on Helicobacter pylori presence and gastric histopathologic changes - Vildan TAŞKIN; Murat SEDELE; Osman SAKA; Bülent KANTARÇEKEN (Turkish Journal of Gastroenterology, 2019)
-